Unveiling the Impact of Anaerobic Soccer Training and Small-Sided Games on Soccer Player’s Body Composition - Mochammad Ilham Ramadhani; David Agus Prianto; I Dewa Made Aryananda Wijaya Kusuma; Dewa Ayu Praba Amustikarani; Alex Aldha Yudi; Ketut Chandra Adinata Kusuma (Physical Education Theory and Methodology)
Background. While soccer research has concentrated on enhancing physical, technical, tactical, and mental abilities, this study uniquely shifts the focus to body composition, a relatively unexplored area, particularly among amateur soccer players.